Influence of stress on the electromechanical properties and the phase transitions of lead-free (1-x)Ba(Zr0.2Ti0.8)O-3-x(Ba0.7Ca0.3)TiO3 - Gadelmawla, Ahmed; Dobesh, David; Eckstein, Udo; Grübl, Oliver; Ehmke, Matthias; Cicconi, Maria Rita; Khansur, Neamul Hayet; de Ligny, Dominique; Webber, Kyle Grant (Journal of Materials Science, 2022)
The influence of stress on the phase boundaries of polycrystalline lead-free perovskite (1 - x)Ba(Zr0.2Ti0.8)O-3-x(Ba0.7Ca0.3)TiO3 (x = 0.4, 0.5, and 0.6) was characterized through the temperature- and stress-dependent small-signal dielectric and piezoelectric response from - 150 to 200 degrees C under uniaxial compressive stress up to - 75 MPa. For all three compositions, the phase transition temperatures separating the rhombohedral, orthorhombic, tetragonal, and cubic phases were shifted to higher temperatures with an increase in the uniaxial mechanical loading, corresponding to a significant decrease in the dielectric and piezoelectric responses. Additional stress-dependent relative permittivity measurements up to - 260 MPa were conducted at four different constant temperatures (- 10, 10, 25, and 40 degrees C), revealing significant increases in the dielectric response, making these materials interesting for tunable dielectric applications. Furthermore, the stress-induced shift in phase transition temperatures was confirmed by in situ combined temperature- and stress-dependent Raman spectroscopy measurements under different constant uniaxial loads within the temperature range from 30 to 130 degrees C.
CRIS-Team WoS Importer:2022-09-16